Penguatan Kompetensi Bahasa Inggris Siswa Sekolah Dasar melalui Metode Active Learning: Pengabdian di SDIT Al-Muthmainnah Kota Jambi - Adang Ridwan; Siti Munawaro; Erdiyan Saputra; Maryanti Sawitry (Jurnal Pengabdian Masyarakat, 2025)
English proficiency at the elementary school level is often still low due to monotonous teaching methods that do not fully engage students in the learning process. This condition highlights the need for innovative teaching strategies that can encourage greater student participation. This community service activity aimed to strengthen the English competence of fifth-grade students through the implementation of the Active Learning method at SDIT Al-Muthmainnah, Jambi City. The program was carried out using a participatory approach through three main stages: planning, implementation, and evaluation. Activities included assisting teachers in designing lesson plans, conducting classroom learning based on Active Learning, and evaluating the outcomes of the program. The results showed that the application of Active Learning successfully enhanced student engagement, improved vocabulary mastery, and fostered students’ confidence in using basic English for communication. Moreover, teachers gained valuable experience in creating a more interactive, creative, and enjoyable learning environment. The implication of this activity is that the Active Learning method can serve as an alternative strategy for teaching English at the elementary level, as it has proven effective in strengthening students’ competencies while supporting a more participatory and meaningful learning process.